2019
DOI: 10.3390/sym11080989
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Modality of Internet Technology on Reliability Analysis and Trust Perception for International Purchase Behavior

Abstract: The proliferation of Internet technology and balance of composition in major feature of many visual products have been advantageous for businesses and changed the distribution channels through which industries reach their consumers. The intensive development of Internet technology and the increasing popularity of online shopping have further changed customers’ purchasing behaviors and the methods by which companies disseminate their video advertisements. The main research question that this study intends to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Online buying impulsiveness was considered a situational trait, impulsive people being emotionally attracted to objects, seeking immediate gratification in the online environment and having difficulties in handling the pressure of inhibiting factors [49]. Improvements in information technologies have led to a higher frequency of online shopping activities, which could explain the expansion of impulsive buying behaviours, as website quality is very important for consumers' online buying impulsiveness [50,51].…”
Section: Personality Antecedents Of Online Buying Behaviourmentioning
confidence: 99%
“…Online buying impulsiveness was considered a situational trait, impulsive people being emotionally attracted to objects, seeking immediate gratification in the online environment and having difficulties in handling the pressure of inhibiting factors [49]. Improvements in information technologies have led to a higher frequency of online shopping activities, which could explain the expansion of impulsive buying behaviours, as website quality is very important for consumers' online buying impulsiveness [50,51].…”
Section: Personality Antecedents Of Online Buying Behaviourmentioning
confidence: 99%
“…What is worth emphasizing is that the affiliate program allows the publisher to have control over the form of advertising (banner, mailing, or the entire website), and over the customers who receive the advertisements. At this stage, this solution seems to be the best, which limits the use of adblock extensions that block advertisements and at the same time emphasizes the benefits of partners' cooperation for a sustainable advertising market [45].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported "Behavior Modality of Internet Technology on Reliability Analysis and Trust Perception for International Purchase Behavior" [17]. The main research question that this study intends to answer is, "What do users do when a YouTube advertisement appears?…”
Section: Lan Et Al Reported "Symmetric Modeling Of Communication Effectiveness and Satisfactionmentioning
confidence: 98%